Prevalence of urinary tract infections and antibiotics susceptibility pattern among infants and young children in Erbil city - Saeed, Chiman Hameed; AL-Otraqchi, Kamal I. B.; Mansoor, Isam Y. (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and objectives: A urinary tract infection is defined by the presence of an organism in the urinary tract that is usually sterile. The age and gender are important factors influencing prevalence of urinary tract infections. The aim of this study was to clarify the microbiology of urinary tract infection, antibiotics susceptibility pattern prevalence and their relation with age, gender and circumcision among infants and young children in Erbil city.Methods: Urine samples were collected from 300 children with sign and symptoms of urinary tract infection at Rapareen Pediatric Hospital in Erbil city. The specimens were cultured on appropriate media and the isolated organisms identified with a significant growth 105 CFU/ml. The susceptibility of bacteria causing urinary tract infection to different antimicrobial agents was investigated.Results: The study showed that 43.3% of children had urinary tract infection (53.2% females, 30.2% males). The highest percentage of infection occurred at age group 6-10 years with female's predominance. The percentage of urinary tract infections in uncircumcised boys was 76.9%. The most common organism isolated was Escherichia coli (33.8%). The isolated bacteria were highly sensitive to Ciprofloxacin, Amikacin and Nitrofurantoin.Conclusion: Early and appropriate diagnosis of urinary tract infection in infants and young children is important as it is marker for urinary tract problems. Escherichia coli was the most common organism causing urinary tract infection in children. The most of urinary isolates had high level of resistance to commonly used antibiotics.